Hubungan antara Kualitas Tidur dan Tingkat Stres dengan Gangguan Siklus Menstruasi - Gracia Feyta Rumagit; Achmad Paturusi; Nancy Bawiling (Jurnal Ilmiah Kesehatan, 2025)
Menstrual cycle irregularities in female students are influenced by factors such as sleep quality and stress levels. This study aims to determine the relationship and provide solutions so that students' reproductive health is maintained. This study aims to determine the relationship between sleep quality and stress levels with menstrual cycle disorders in Public Health Science students, Class of 2021, Manado State University. The method used is descriptive correlation through a Cross-sectional approach. The respondents in this study population were 59 female students. The results showed that sleep quality and stress levels with menstrual cycle disorders p = 0.00 <0.05. The conclusion of this study states that there is a relationship between sleep quality and stress levels with menstrual cycle disorders in public health students of the 2021 batch of Manado State University. Suggestions Public Health Students of the 2021 Batch of Manado State University are expected to regulate sleep habits with a consistent schedule, create a comfortable atmosphere, avoid gadgets and heavy foods before bed, and limit caffeine. In addition, implement a healthy lifestyle by consuming nutritious foods, exercising regularly, and getting enough rest. Time management and academic load are also important so that sleep quality and stress can be maintained, supporting the stability of the menstrual cycle and overall reproductive health.